THE EFFECT OF MARKETING STRATEGY AND COMMUNITY PERCEPTION OF DECISIONS TO CHOOSE ISLAMIC JUNIOR HIGH SCHOOL IN JAMBI PROVINCE - Mahmud, Mahmud (Dinasti Publisher, 2019)
This study aims to analyze the effect of Marketing Strategy and Community Perception on the Decision of Choosing Islamic Junior High School in Jambi Province both partially and simultaneously. The population in this study is the community who send their children to private Tsanawiyah Madrasahs in Jambi Province representing 3 regions with 178 people. Quantitative analysis method using path analysis, followed by analysis of determination (R Square), partial hypothesis testing (t test) and simultaneous (F test) with alpha 5 percent (0.05). Before further analysis, the analysis requirements test is carried out first. Analysis tools using SPSS Version 21.0 for Windows. The results showed that marketing strategies and public perceptions had a positive and significant effect on the decision to choose Islamic Junior High School in Jambi Province.